Aorto-occlusive disease causing pregnancy complications: A serendipitous diagnosis (Indian Journal of Case Reports, 2019)
Takayasu arteritis or pulse-less disease is known to present in myriad forms. Here, we report the case of a 22-year-old young pregnant female who presented to us with pregnancy complications was finally diagnosed to have Takayasu Arteritis but not before her disease course took a lot of diagnostic turns. It highlights the fact that the disease is very variable in its presentation. The other unique presentations reported in literature along with a brief review of the treatment options are also given.